2010
DOI: 10.1007/s10533-010-9490-x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of oxidized and reduced iron in a northern hardwood forest

Abstract: Iron (Fe) is ubiquitous in forest ecosystems and its cycle is thought to influence the development of soil, particularly Spodosols (podsolization), and the biogeochemistry of macro-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 62 publications
6
18
0
Order By: Relevance
“…These Fe oxidizers that thrive in circumneutral pH environments take advantage of thermodynamic gradients at interfaces between low O 2 (where Fe (II) is stable) and higher O 2 (Konhauser et al, 2011). Oxidation of Fe in the early growing season has been well documented at redox transition zones in surface waters of first‐order watersheds (Emerson et al, 2010; Fuss et al, 2010; Knorr, 2013). It is also likely that the interior of soil aggregates serve as similar redox gradients, where these Fe‐oxidizing bacteria could facilitate oxidation of Fe (II) in the solid and dissolved phase within aggregates as soil drains through the early growing season.…”
Section: Discussionmentioning
confidence: 99%
“…These Fe oxidizers that thrive in circumneutral pH environments take advantage of thermodynamic gradients at interfaces between low O 2 (where Fe (II) is stable) and higher O 2 (Konhauser et al, 2011). Oxidation of Fe in the early growing season has been well documented at redox transition zones in surface waters of first‐order watersheds (Emerson et al, 2010; Fuss et al, 2010; Knorr, 2013). It is also likely that the interior of soil aggregates serve as similar redox gradients, where these Fe‐oxidizing bacteria could facilitate oxidation of Fe (II) in the solid and dissolved phase within aggregates as soil drains through the early growing season.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in the annual grassland and drained peatland soils, where Fe reducing conditions likely occur only episodically for short durations following large rain events, Fe reduction rates peaked after three days. These hot moments can be important to overall ecosystem function as evidenced by higher-thanexpected Fe(II) concentrations in well-drained soils at the Hubbard Brook experimental forest (Fuss et al 2011), which contribute to soil C stabilization at that site.…”
Section: Discussionmentioning
confidence: 99%
“…In humid tropical forest soils, Fe reduction dominates anaerobic respiration in laboratory experiments (Chacon et al 2006), and Fe(II) was observed at relatively low moisture contents in the field (Hall et al 2013). Even in well-drained, seemingly oxic spodosols in temperate forests, the soil solution can contain up to 60 % Fe(II) (Fuss et al 2010). Redistribution of Fe(II) across persistent anaerobic-aerobic interfaces, creating redoximorphic features in the process (Jacobs et al 2002;Richter et al 2007;Fimmen et al 2008), provides further evidence for the importance of anaerobic Fe reduction in upland soils.…”
Section: Evidence For Anaerobic Metabolism In Upland Soilsmentioning
confidence: 99%
“…Nevertheless, Fe reduction is increasingly recognized as the quantitatively most important anaerobic respiratory pathway in a large range of upland soil ecosystems because of its abundance relative to other TEAs (Schuur and Matson 2001;Miller et al 2001;Chacon et al 2006;Fuss et al 2010;Thompson et al 2011;Hall et al 2013 Nutrients (e.g., N and P)…”
Section: Evidence For Anaerobic Metabolism In Upland Soilsmentioning
confidence: 99%